(untitled) (Scientific journal of the Fergana State University, 2024)
This article discusses the types of antonyms, their use in fiction, as well as in religious texts. One of the manifestations of consistency in vocabulary is the category of antonymy. The interest in the study of this category observed in modern linguistics is explained, on the one hand, by increased attention to the semantic aspect of language, and on the other hand, by the development of research into phenomena that confirm the thesis about the systemic nature of language. The study of antonymy at the present stage is characterized by a constant search for techniques to make the analysis of antonyms more effective. There is a certain shift in emphasis in the study of antonymy - from the general linguistic plan to the specific speech embodiment of antonymy, and therefore the subject area of ​​research is expanding: specific antonymic series and their functional properties are analyzed.